Dynamic analysis of steel frames subjected to impulse loads - Nur Uzmaizzati, Muhammad Yusof (2019)
Impulse loads are loading that are subjected on structures in a very short time. These types of loads are commonly associated with blast loads, which are generated from blast pressures from chemical explosions. The response of structures subjected to impulse loads can be studied using experimental and numerical approaches. However, experimental studies require stringent safety procedure and can be costly. Therefore, numerical modelling is an alternative approach, which is the aim of this study. This study is interested investigating the response of steel frames subjected to impulsive loading using finite element (FE) analysis. One of the objectives of this study is to develop a finite element codes using OCTAVE to predict the response of steel frames when subjected to various impulse loads. So, this paper present the dynamic analysis of steel frames subjected to impulse loads. The analysis is performed using finite element method. Finite element source codes were developed using OCTAVE, a programming language software, to investigate the dynamic behaviour of the steel frames. The results from the developed source codes are validated against the result from a commercial finite element software, ABAQUS, where satisfactory results are obtained. From this study, the types of support influenced the dynamic behaviour of the steel frames when subjected to different explosive weights at various standoff-distances